The moral economy of selfhood and caring: negotiating boundaries of personal care as embodied moral practice - Chattoo, Sangeeta; Ahmad, Waqar I.U. (Sociology of health & illness, 2008)
This paper engages with the dichotomous notions of caring underpinning social policy and practice in Britain, that splits up the ‘carer’ and ‘cared for’ into autonomous, unitary subjects, by locating personal care as an embodied, moral practice within a theoretical framework of relational ontology. Drawing on empirical accounts and narratives related to personal care within the context of advanced cancer, we argue that personal care involves negotiation of boundaries between notions of relatedness and legitimate dependence on one hand, and independence and integrity of the embodied self on the other; and we analyse how these boundaries are informed by particular cultural or religious scripts on gender, relatedness, conjugality and filial obligations. The paper draws on data and analysis based on observations and in‐depth interviews with White and South Asian participants between 19 and 89 years of age receiving treatment for cancer, and family members closely involved in their personal care. In using a comparative method for analysis and understanding caring as an embodied moral practice and site of subjectivity across cultural/religious groups, it is suggested that ethnicity is not necessarily the only useful analytical concept to explore the illness and caring experiences of research participants from minority ethnic backgrounds.